KLASIFIKASI BISNIS E-COMMERCE DI INDONESIA - Mahir Pradana (Modus, 2015)
Today, Indonesian people in urban areas has strong engagement to internet. Almost every activities are necessarily involves the internet and information technology. So, no wonder if the internet now are very demanding to society. This phenomena also arising the enablement of business that using internet as main platform or known as e-commerce. E-commerce is defined as the process of purchasing, sales, transfer or exchange products, services or information via computer network over the internet. With business activity in e-commerce, it can be extending activity and reach consumers more easily. Also the process of transactions are so far in nature conventional modernized by providing online transaction. This article is intended to analyze and discuss about the types of business e-commerce in Indonesia based on the phenoimena and development of the theory underlying information system. Keywords: E-commerce, management information system, users satisfaction, webqual